IMPLEMENTATION OF THE SPECIAL SOCIAL REHABILITATION PROGRAM FOR ADOLESCENTS IN OVERCOMING SOCIAL WELFARE - Andrean Putra Sinaga; Wiro Oktavius Ginting (Jurnal Kebijakan Publik, 2025)
Economic problems are a complex problem in the city of Medan, which makes some people forced to make a living on the streets. The Medan City government's efforts to overcome street children are by issuing Regional Regulation No. 6 of 2003 concerning the Prohibition of Homeless and Begging for the Immoral in Medan City. This study aims to analyze and describe the implementation of the Social Rehabilitation Program Policy for Children and Adolescents in overcoming the problem of social welfare services in the city of Medan. The research method used is descriptive research with a qualitative approach. Data collection was carried out by interview, observation and documentation techniques. The data obtained is analyzed qualitatively with a theoretical approach to policy implementation proposed by Smith (1973) including 4 indicators, namely Idealized policy, target group, implementing organization, and environmental factor. The results of the study show that the implementation of the Social Rehabilitation Policy for Children and Adolescents in overcoming the Social Welfare Service Authority in the city of Medan in carrying out the program is running well and in accordance with its duties and functions. However, coordination between the Medan City Social Service and the sub-district and sub-district in socializing PPKS problems in each region in handling it is important. It is hoped that the Medan City Social Service will soon have a social protection house